Design and fabrication of adjustable ceiling fan blade cleaner - Muhamad Rusydi, Ali (2007)
This thesis is based on the project about design and fabrication of adjustable ceiling fan blade cleaner. 'Adjustable Ceiling fan blade cleaner' is equipment that can clean the blade ceiling fan. The fabrication of this product started with surveying in market about the product, specification analysis, concept designing, detail concept designing and fabrication of the product. Four (4) products were selected from the market for the analysis and investigation. One types of the product that suitable and fit all the specification was chosen to fabricate. The investigation was made in scope of the constraint that may occur for the development of the product and relevance of the product manufacturing processes. This product have been fabricate according to engineering method through many fabrication process such as welding, cutting, drilling and assembling. For development of this project and future works, some suggestion was made for upgrading the product. The suggestion like dust case and more durable of the holder to make sure this product will competitive with the existing products in the market.